PELATIHAN PEMBUATAN PERLENGKAPAN RUMAH MENGGUNAKAN HOLLOW BAJA RINGAN DI DESA KARANGJAYA - Wawan Giri Saputra; M. Ilyas Sikki; Setyo Supratno (An-Nizam, 2023)
Training for making home furnishings using light steel hollows in Karangjaya Village focuses on transferring technological and expertise developments to improve human resource development related to conceptual (ideas or ideas for using hollows and designing) and technical skills (calculating the amount of material, measuring shelf length, cutting, and assembling materials into finished goods. Providing supplies to the public with material and knowledge about various uses of mild steel that can be utilized, is expected to be a motivation for the younger generation in particular and the community to improve skills which hopefully will be useful in the future. Results that can be made in this training is a book wall shelf that will be given by the local madrasah as a place for books and the Qur'an as a form of support for the group 19 literacy program in Karangjaya village.